Global Health Security in the Age of Transnational Malicious Cyber Operations: A Taxonomic Analysis of Non-State and State- Backed Cyber Threats - Temirbekov, Zh. (Право и государство №2 (103), 2024)
The paper emphasises the critical nature of the cybersecurity threats to the global healthcare sector. The examination of quantitative and qualitative research results from official reports, bulletins, and journals is combined in the study to demonstrate the scope and impact of non-state and state-backed malicious cyber operations directed at healthcare systems. In today’s digital age, cyber operations against the healthcare sector are increasing in rate and becoming more sophisticated. Therefore, the paper is relevant. The paper’s subject is analysing the nature, scope, and consequences of malicious cyber activity; it examines how it can impact healthcare systems, patient privacy, and public health. By analysing recent incidents, conducting a taxonomic analysis, and proposing some general strategies to enhance healthcare protection in the face of cybersecurity threats, the paper sheds light on the critically important issue of cybersecurity threats in the healthcare sector, which is the purpose of the paper. The study’s novelty is that this paper offers a taxonomic analysis of cybersecurity threats that provides a struc- tured framework to understand the threats and propose some general suggestions to enhance the protection of the global healthcare sector. Brief conclusions: 1) State-backed malicious cyber operations can significantly compromise the quality of healthcare and patient safety; 2) Decision-making centers in the healthcare sector are recommended to pay attention to the need to modernize cybersecurity policies since, as studies show, more and more healthcare organisations are becoming victims of transnational malicious cyber operations.
Keywords: malicious cyber operations, data privacy, right to health, global health, health-care, cyber-attack resilience, healthcare infrastructure, cybersecurity, cyber threat taxonomy